PHOSPHORUS SOURCES IN THE GROWTH AND QUALITY OF COFFEA ARABICA SEEDLINGS PRODUCED IN TUBES - Levy Tadin Sardinha; Andre Cabral França; Caroline Maira Miranda Machado; Brendo Oliveira Ferreira; Leandro Alves Macedo; Rafaele Sousa Cruz; Samuel Dias Moreira; Fausto Henrique Vieira Araújo (Colloquium Agrariae, 2023)
The objective of this study was to evaluate the growth and quality of arabica coffee seedlings produced in tubes under different sources of phosphorus. The experiment was conducted in a greenhouse in a randomized block design with eleven treatments and four replications, three plants per plot. The dose of organomineral, MAP and MAP coated was based on the recommendation of P2O5 for the formation of coffee seedlings.. For Osmocote, the manufacturer's recommendation was used depending on the amount, in dm³, of substrate. After 180 days of transplanting, the growth characteristics of the plants (leaf dry matter, stem and roots) were evaluated, and the aerial part and root system ratio and Dickson's quality index were calculated, as well as regression equations were adjusted for the evaluated parameters. For the growth and quality of seedlings, it was observed that in fertilizations with pelleted and branched organomineral, coated MAP and Osmocote, the highest averages were obtained for the contents of dry matter, height, diameter of the collection and quality indexes, when compared to the other sources of P2O5.. The dose that provides the maximum growth and quality of coffee seedlings for the treatments with organomineral was calculated, this being equal to 6 g/dm³ of P2O5 for bran and pelleted organomineral.  According to the results, the sources that promoted the formation of a vigorous seedling, with an adequate supply of nutrients and a good quality standard are pelleted organonineral fertilization and MAP, reducing the risk of losses and consequently the need to discard the seedlings in the nursery.